Collaborative digital libraries: A model for the support of smart instruction and learning - Abrizah, Abdullah; Edzan, N.N. (2002)
This paper describes the conceptualisation of a model for digital libraries for Malaysian schools, which supports classroom instructions and learning. Malaysia is rich in her national heritage of published and unpublished works - biographical repositories, art works, students' projects, etc. - that can support and enrich instruction and learning in a smart environment. Digital libraries play a major role in the Smart Education environment as the central concern is in providing fast and easy access to digital information resources without the constraints of time and geographic boundaries. The move towards collaboratively building the content of a digital library is a fairly recent trend. Collaborative digital libraries simulate an environment where partners are empowered to participate in building and up keeping the knowledge content of the system. A model of a collaborative digital library incorporates five basic features: a) uploading and indexing, that support creation, capturing and sharing of learning objects from distributed sites and user groups; b) supporting multi-format digital resources; c) searching and retrieval of contents of stored objects; d) provision of user control display; and e) basic security to control user access and protect library contents. The conceptualisation of Malaysian digital libraries must address issues such as identifying local resources, ascertaining the needs of it users, and establishing a framework plausible to meet these needs. It may be approached through the establishment of test beds in a particular learning institution, before wider implementations.